Personal anxiety - the determinant of the anthropometric and functional status of female students - Romanenko Valerij Aleksandrovich; Krainya Natal'ia Vladimirovna; Mosenz Valerij Alekseevich; Prikhodko Vladimir Mikhajlovich (Kharkov National Pedagogical University, 2011)
We consider the problem of dependence of the physical status of the students on their level of personal (genetic) anxiety. The experiment involved 105 students aged 19-21 years. It is shown that between anxiety and performance of the genetic status of the students there anthropometric and functional ambiguous dependence. These relationships are determined by the peculiarities of somatotype, the oxygen-transport system and the mechanisms of energy. It is established that anxious students are characterized low level of physical development, insufficient capacity of the cardiorespiratory system. This corresponds to the same level of physical performance, aerobic capacity and resistance to hypoxia. These patterns remain when evaluating the power and capacity of the glycolytic mechanism of energy and non-anxious in anxious students.